2022
DOI: 10.3389/fnbeh.2022.910056
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted development from head to tail: Pervasive effects of postnatal restricted resources on neurobiological, behavioral, and morphometric outcomes

Abstract: When a maternal rat nurtures her pups, she relies on adequate resources to provide optimal care for her offspring. Accordingly, limited environmental resources may result in atypical maternal care, disrupting various developmental outcomes. In the current study, maternal Long-Evans rats were randomly assigned to either a standard resource (SR) group, provided with four cups of bedding and two paper towels for nesting material or a limited resource (LR) group, provided with a quarter of the bedding and nesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 107 publications
(107 reference statements)
1
2
0
Order By: Relevance
“…Our results showed that LBN altered maternal nursing behaviors and resulted in smaller pup weight at P3 compared to control pups. Similarly, Kent et al 36 found that low bedding was associated with decreased pup weight at P9 and P21 suggesting LBN may employed LBN in the antenatal and postnatal period while many previous studies have used a classic postpartum LBN approach which may be why our results were only partially consistent with previous LBN studies. 38,39 Additionally, the small amount of nesting materials in addition to the lack of bedding may explain some of the differences observed as previous studies have found that reduced nesting materials alone are sufficient to induce maternal stress and anxiety.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Our results showed that LBN altered maternal nursing behaviors and resulted in smaller pup weight at P3 compared to control pups. Similarly, Kent et al 36 found that low bedding was associated with decreased pup weight at P9 and P21 suggesting LBN may employed LBN in the antenatal and postnatal period while many previous studies have used a classic postpartum LBN approach which may be why our results were only partially consistent with previous LBN studies. 38,39 Additionally, the small amount of nesting materials in addition to the lack of bedding may explain some of the differences observed as previous studies have found that reduced nesting materials alone are sufficient to induce maternal stress and anxiety.…”
Section: Discussionsupporting
confidence: 73%
“…Our results showed that LBN altered maternal nursing behaviors and resulted in smaller pup weight at P3 compared to control pups. Similarly, Kent et al 36 found that low bedding was associated with decreased pup weight at P9 and P21 suggesting LBN may result in direct weight gain effects in offspring. LBN had no effect on pup retrieval or hoarding behavior in the present study.…”
Section: Discussionmentioning
confidence: 88%
“…Five of them using the wire‐floored Limited Bedding & Nesting paradigm found more anxiety behavior in a light‐dark box in both sexes of mice (Demaestri et al., 2020), reduced anxiety in male but not female rats in EPM and open field tests (Prusator & Greenwood‐Van Meerveld, 2015), no effects on open‐arm behavior in an EPM on rats of either sex but reduced open‐field center time in males (Guadagno et al., 2018), and no effects on EPM or open‐field behavior for male or female mice (Goodwill et al., 2019; Manzano‐Nieves et al., 2018). In a study using a bedding Scarcity model similar to that used here, there was no effect on EPM behavior in male or female rats (Davis et al., 2020), but more thigmotaxis in an open field in females (Kent et al., 2022). Studies involving only males found that previous Limited Bedding & Nesting produced higher anxiety in a light‐dark box, but not in an open field (Bolton et al., 2018; Yang et al., 2015) or EPM (Wearick‐Silva et al., 2019).…”
Section: Discussionmentioning
confidence: 66%